Fluid-structure interactions of variable span wings in low Reynold flows - Salleh, Hafiz; Saharin, Sanisah; Azmi, Mohammad Hanafi; Khan, Sher Afghan (Science Publishing CorporationPublisher of International Academic Journals, 2018)
Numerical method is one of the method which is applied to study the aerodynamics of static variable span morphing wing and to evaluate flow structure over the wing surface (especially leading edge) at different low reynolds number/flow. The numerical result of lift coefficient vs span increment (pencentage) is validated with experimental result from previous study. Effect of the change of wingspan on low Reynold number/flows is investigated for the wing lift coefficient, and aerodynamics efficiency. Some contour results including pressure contour is observed. The pressure contour along wingspan from each case is figured out.